Uncommon allies: American Jews and Christians uniting against Hitler, 1933-1945 - Shore, Alan M. (Syracuse University Press, 2024)
In Uncommon Allies, Alan Shore uses an impressive range of primary and secondary sources, including English and Yiddish newspapers of the time and neglected histories of various religious organizations, to shine a light on pivotal rallies against the rise of fascism in Germany which took place in Madison Square Garden between 1933-1945